Perlindungan Hukum Terhadap Data Pribadi di Era Big Data - Rahmah, Siti; Darmiwati; Wahyuni, Fitri (Jurnal Indragiri Penelitian Multidisiplin, 2024)
The increasingly massive use of information and communication technology has raised concerns about protecting personal data in the era of big data which can harm individuals. Big Data as a form of technological development has not been balanced with developments in legal regulations, so there is no harmony between the use of Big Data and legal regulations related to the protection of personal data. Regulations related to the protection of personal data that already exist in Indonesia cannot guarantee and protect confidentiality and overcome the problem of protecting citizens' personal data. This is because the existing regulations are still general, partial and sectoral so they cannot guarantee optimal legal certainty for the protection of personal data. Therefore, it is important for Indonesia to have special regulations regarding the protection of personal data. Strengthening personal data protection is a necessity in the big data era, therefore, it is necessary to improve relevant laws and regulations, Law Number 27 of 2022 concerning Personal Data Protection. is the newest and most comprehensive regulation and is effective in protecting personal data in the big data era if it is implemented consistently and supported by an effective independent supervisory institution for Personal Data Protection, to ensure personal data is processed in a legal and responsible manner. Apart from that, educational efforts and increasing public awareness are needed about the importance of protecting personal data.